Effects of Boron-Incorporation in a V-Containing Zr-Based AB2 Metal Hydride Alloy - Shiuan Chang; Kwo-Hsiung Young; Taihei Ouchi; Jean Nei; Xin Wu (Batteries, 2017)
In this study, boron, a metalloid element commonly used in semiconductor applications, was added in a V-containing Zr-based AB2 metal hydride alloy. In general, as the boron content in the alloy increased, the high-rate dischargeability, surface exchange current, and double-layer capacitance first decreased and then increased whereas charge-transfer resistance and dot product of charge-transfer resistance and double-layer capacitance changed in the opposite direction. Electrochemical and gaseous phase characteristics of two boron-containing alloys, with the same boron content detected by the inductively coupled plasma optical emission spectrometer, showed significant variations in performances due to the difference in phase abundance of a newly formed tetragonal V3B2 phase. This new phase contributes to the increases in electrochemical high-rate dischargeability, surface exchange current, charge-transfer resistances at room, and low temperatures. However, the V3B2 phase does not contribute to the hydrogen storage capacities in either gaseous phase and electrochemical environment.